2015
DOI: 10.1371/journal.pone.0122085
|View full text |Cite
|
Sign up to set email alerts
|

The Pet Factor - Companion Animals as a Conduit for Getting to Know People, Friendship Formation and Social Support

Abstract: BackgroundWhile companion animals have been previously identified as a direct source of companionship and support to their owners, their role as a catalyst for friendship formation or social support networks among humans has received little attention. This study investigated the indirect role of pets as facilitators for three dimensions of social relatedness; getting to know people, friendship formation and social support networks.MethodsA telephone survey of randomly selected residents in four cities, one in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
130
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 210 publications
(155 citation statements)
references
References 35 publications
6
130
0
3
Order By: Relevance
“…These findings support research with non-disabled individuals (see for example McNicholas and Collis 2000;Wood et al 2015) and individuals with physical disabilities (see for example Fairman and Huebner 2000;Shyne et al 2012), which found the dog acted as a social stimulant, with members of the community often initiating contact to ask questions about the dog. Furthermore, there was some evidence to support previous research that a dog helped to reduce the negative effects of social ostracism (see for example Shyne et al 2012) and increased individual's confidence (Hart et al 1987).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These findings support research with non-disabled individuals (see for example McNicholas and Collis 2000;Wood et al 2015) and individuals with physical disabilities (see for example Fairman and Huebner 2000;Shyne et al 2012), which found the dog acted as a social stimulant, with members of the community often initiating contact to ask questions about the dog. Furthermore, there was some evidence to support previous research that a dog helped to reduce the negative effects of social ostracism (see for example Shyne et al 2012) and increased individual's confidence (Hart et al 1987).…”
Section: Discussionsupporting
confidence: 82%
“…; Wood et al . ). For example, in an Australian survey, 58% of pet owners indicated they had got to know people and made friends through having pets (McHarg et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In this respect, emphasis is often placed on family, friends, and social interaction with other people [810]. However, the role of pets is likely to have been under-acknowledged, with indications in research that some people consider their pets as being as important as family members, and their value in terms of companionship, love and support is widely acknowledged [11]. Analysis of an individual’s support network suggests a unique contribution from pets that extends beyond the support and connections provided by familial, friendship and weak tie connections.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, they act as social catalysts and help build and maintain social networks. Individuals with pets are more likely to know their neighbors, and about 40% of owners reported receiving social support from people they met through their companion animals (Wood et al, 2015). Among communitydwelling older adults, pets stimulate communication (Rogers, Hart, & Boltz, 1993) and often serve as a conversation topic (Rosenkoetter, 1991).…”
Section: Benefits Of Pet Ownership In Older Adulthoodmentioning
confidence: 99%